(untitled) (Педагогіка вищої та середньої школи, 2001)
This article is devoted to the problem of humanization of the educational system and the process of formation of communicative skills of teachers to be. The author emphasizes the importance of humane relations in the “teacher-pupil” system in the educative process at the level of higher-school education.